Provable Security of Symmetric-key Cryptographic Schemes - Jha, Ashwin (Kolkata: Indian Statistical Institute, 2019)
In this thesis, we provide quantitative and/or qualitative improvements in the provable security of several symmetric-key schemes, encompassing major information security goals, viz. data authentication, encryption, and authenticated encryption.
Introduction -- Preliminaries -- Pseudorandom Permutation based CBC-MAC Family -- Pseudorandom Function based CBC-MAC Family -- Counter-based Input Encoding in MACs -- Tweakable Pseudorandom Permutation based Online Ciphers -- Security of Cascaded LRW2 -- Random Read Access in OCB -- Graphs and Probability Theory
Thesis (Ph.D.) - Indian Statistical Institute, 2019
Guided by Prof. Mridul Nandi
Keywords: Cryptography; Symmetric-key Security; Data Encryption; Provable Security; MAC; AEAD; CBC-MAC; OCB; Cascaded LRW2